1995
DOI: 10.1002/art.1780380615
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐spin relaxation of brain tissues in systemic lupus erythematosus

Abstract: Objective. To correlate the spin-spin relaxation time (T2) of brain tissue in neuropsychiatric systemic lupus erythematosus (NPSLE) with the patient's clinical condition.Methods. T2 values were determined in 54 SLE patients and 45 non-SLE cointrols at 1.5 Tesla, using intensity from multi-echo magnetic resonance (MR) images fitted to an exponential decay curve with rateconstant T2.Results. The T2 of white matter was increased in SLE patients compared with controls (P = 0.01) and was increased in those patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 31 publications
0
20
0
1
Order By: Relevance
“…All patients received careful neurological and rheumatological examinations. Patients were classified as major or minor NPSLE based on the method of Carbotte et al (8,(17)(18)(19). Some patients with minor symptoms had previously suffered major episodes that had resolved at the study time.…”
Section: Study Populationmentioning
confidence: 99%
See 3 more Smart Citations
“…All patients received careful neurological and rheumatological examinations. Patients were classified as major or minor NPSLE based on the method of Carbotte et al (8,(17)(18)(19). Some patients with minor symptoms had previously suffered major episodes that had resolved at the study time.…”
Section: Study Populationmentioning
confidence: 99%
“…Eighty individual volume measurements were taken in normalappearing frontal GM, and mean (trimmed mean) T 2 values were calculated for each patient using a 10% trimming process to reduce further the probability of volume averaging with white matter (WM) or CSF (8). To minimize partial volume effects, volumes were selected away from apparent tissue borders and focal lesions.…”
Section: Manual T 2 Determinationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using magnetic resonance spectroscopy (H-MRS) we have reported that normal-appearing brain tissue in previously active NPSLE is characterized by the loss of the neuronal marker N-acetylaspartic acid (NAA) and the presence of cerebral atrophy, findings indicative of diffuse neuronal loss due to a potent neurotoxic process and the observation of increased lactate/lipid in NPSLE patients (Sibbitt 1993). More recently, using Sl data we have reported reduced NAA in focal lesions in NPSLE (Brooks, 1995). This study serves to expand on these previous findings by investigating the neuroiiietabolic status of NPSLE patients with active, major neurological dysfunction versus minor neurological dysfunction and address the issue of enhanced lactate using both short and long echo spectroscopy.…”
Section: Introductionmentioning
confidence: 66%